2017
DOI: 10.1249/mss.0000000000001357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HSCT Conditioning and Glucocorticoid Dose on Exercise Adherence and Response

Abstract: Exercise adherence during inpatient period is significantly affected by dose of GC treatment but not by condition regimen. However, given the reasonable adherence rates also in the GC-high group, data support the feasibility and importance of exercising for all allo-HSCT patients during the inpatient period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Despite the health-related challenges that patients face after receiving allo-HSCT, they tend to have a relatively high adherence rate to physical exercise. One study showed that the adherence rate to a physical exercise plan of five sessions weekly during the inpatient period was 64% in myeloablative conditioning, 54% in reduced-intensity conditioning, and 63% in nonmyeloablative conditioning in 113 allo-HSCT patients 52 . Another study reported a 90% average adherence rate to a supervised multimodal exercise program performed five times per week for four to six weeks during the inpatient period after allo-HSCT in 42 allo-HSCT patients 44 ; similarly, 12 elderly allo-HSCT patients in a different study showed an 85% adherence rate 53 .…”
Section: Feasibility Of Physical Exercise For Allo-hsct Patientsmentioning
confidence: 99%
“…Despite the health-related challenges that patients face after receiving allo-HSCT, they tend to have a relatively high adherence rate to physical exercise. One study showed that the adherence rate to a physical exercise plan of five sessions weekly during the inpatient period was 64% in myeloablative conditioning, 54% in reduced-intensity conditioning, and 63% in nonmyeloablative conditioning in 113 allo-HSCT patients 52 . Another study reported a 90% average adherence rate to a supervised multimodal exercise program performed five times per week for four to six weeks during the inpatient period after allo-HSCT in 42 allo-HSCT patients 44 ; similarly, 12 elderly allo-HSCT patients in a different study showed an 85% adherence rate 53 .…”
Section: Feasibility Of Physical Exercise For Allo-hsct Patientsmentioning
confidence: 99%
“…First, research has shown that allo-HSCT patients conditioned with elevated doses of chemotherapy and radiotherapy exercise for shorter periods of time when compared to patients receiving less aggressive protocols. 49 These patients also experience GVHD and toxicities with more severity and have increased length of cytopenia, 50,51 which translates into higher risk of infections and more isolation days. 52 Second, nearly 90% of the participants who developed GVHD during hospitalization participated in fewer classes.…”
Section: Discussionmentioning
confidence: 99%